Clinical approach to the management of Intestinal Failure Associated Liver Disease (IFALD) in adults: A position paper from the Home Artificial Nutrition and Chronic Intestinal Failure Special Interest Group of ESPEN. Issue 6 (December 2018) - Lal, Simon; Pironi, Loris; Wanten, Geert; Arends, Jann; Bozzetti, Federico; Cuerda, Cristina; Joly, Francisca; Kelly, Darlene; Staun, Michael; Szczepanek, Kinga; Van Gossum, Andre; Schneider, Stephane Michel; et al.
Summary: We recommend that intestinal failure associated liver disease (IFALD) should be diagnosed by the presence of abnormal liver function tests and/or evidence of radiological and/or histological liver abnormalities occurring in an individual with IF, in the absence of another primary parenchymal liver pathology (e.g. viral or autoimmune hepatitis), other hepatotoxic factors (e.g. alcohol/medication) or biliary obstruction. The presence or absence of sepsis should be noted, along with the duration of PN administration. Abnormal liver histology is not mandatory for a diagnosis of IFALD and the decision to perform a liver biopsy should be made on a case-by-case basis, but should be particularly considered in those with a persistent abnormal conjugated bilirubin in the absence of intra or extra-hepatic cholestasis on radiological imaging and/or persistent or worsening hyperbilirubinaemia despite resolution of any underlying sepsis and/or any clinical or radiological features of chronic liver disease. Nutritional approaches aimed at minimising PN overfeeding and optimising oral/enteral nutrition should be instituted to prevent and/or manage IFALD. We further recommend that the lipid administered is limited to less than 1 g/kg/day, and the prescribed omega-6/omega-3 PUFA ratio is reduced wherever possible. For patients with any evidence of progressive hepatic fibrosis or overt liver failure, combined intestinal and liver transplantation should be considered.